Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41368-020-00095-0
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive behavioural assessments in mouse models of temporomandibular joint disorders

Abstract: Orofacial pain or tenderness is a primary symptom associated with temporomandibular joint (TMJ) disorders (TMDs). To understand the pathological mechanisms underlying TMDs, several mouse models have been developed, including mechanical stimulus-induced TMD and genetic mouse models. However, a lack of feasible approaches for assessing TMD-related nociceptive behaviours in the orofacial region of mice has hindered the in-depth study of TMD-associated mechanisms. This study aimed to explore modifications of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Specific functions of the orofacial areas such as bite force could determine the nociception in the deep craniofacial tissues of the animals [ 151 , 206 ]. The validity for usage of bite force in the animals could be explained by the evidence of a reduction of bite force in painful TMD patients [ 207 , 208 ].…”
Section: How To Identify the Pain In The Deep Craniofacial Tissues In The Preclinical Models? ( Table 2 )mentioning
confidence: 99%
“…Specific functions of the orofacial areas such as bite force could determine the nociception in the deep craniofacial tissues of the animals [ 151 , 206 ]. The validity for usage of bite force in the animals could be explained by the evidence of a reduction of bite force in painful TMD patients [ 207 , 208 ].…”
Section: How To Identify the Pain In The Deep Craniofacial Tissues In The Preclinical Models? ( Table 2 )mentioning
confidence: 99%
“…According to previous research, TMJOA manifestations can be observed 3 weeks post-UAC surgery in mice ( Li et al, 2020 ). Therefore, we started bilateral miR-181a-5p ASO injections in the TMJ cavity at the 4th week after UAC, and they were administered twice a week for 6 consecutive weeks.…”
Section: Resultsmentioning
confidence: 71%
“…In the current study unilateral anterior crossbite surgery was performed to simulate malocclusion, which successfully established a stable TMJOA mouse model. In a series of previous studies a sustained abnormal occlusal relationship changed incisal guidance during mastication, resulting in TMJ degenerative and pathological changes, which can mimic TMJOA caused by an abnormal occlusal relationship and excessive joint loading in humans ( Li et al, 2020 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Restoring the normal meal duration can serve as an indicator of the pharmacologic efficacy of anti-inflammatory drugs such as dexamethasone ( 115 ), or capsaicin, a compound known to eliminate C-fibers that participate in the nociceptive pathway ( 114 ). Similarly, mice with temporomandibular joint pain had decreased eating duration and frequency, an effect that was consistent with cartilage degradation, making it a reliable method for pain recognition ( 116 ). Adequate dosage of multimodal analgesic treatments with opioids and non-steroidal anti-inflammatory drugs after a surgical procedure has been shown to preserve food intake in rats undergoing implantation of epidural electrodes ( 117 ).…”
Section: Organic Responses Derived From Pain In Relation To Pain Asse...mentioning
confidence: 97%